The Effect of Season on the Feed Quantity and Quality and Growth Performance of Male Bali Cattle Fattened in Smallholder Farms - Paulus Klau Tahuk; Endang Baliarti; Subur Priyono Sasmito Budhi; Panjono Panjono (Faculty of Animal Science, Universitas Gadjah Mada, 2018)
The research was aimed to determine the effect of season on feed quantity and quality, and growth performance of male Bali cattle fattened in smallholder farms. Observation from January to March for rainy season and June to August for dry season. Feed quantity and quality were observed covering all feedstuff used farmers in fattening. Cattle used for rainy season was 50 heads aged 1.5 – 4.0 years with initial body weight (BW) 188.03±31.85 kg. In dry season, observation was continued for the same cattle as many as 35 heads aged 2.0 – 4.5 years and initial BW was 261.80±38.46 kg. Data were analyzed by quantitative descriptiption for feed quantity and quality, while growth performance were analyzed by independent T-Test. Results of study showed the dominant type of feedstuff used during rainy and dry season were L.leucocephala (56.00 vs 33.14%), Zea mays fresh straw 18.44% (rainy season), natural grass (13.00 vs 22.25%), P.purpuroides (3.68 vs 3.99%) and G.sepium (1.36 vs 29.69%). Crude protein (CP) of L.leucocephala and G.sepium higher during the dry season, while S. grandiflora, natural grass, and P.purpuroides higher in rainy season. The DMD (%) of L. leucocephala and S. grandiflora in rainy and dry seasons were almost the same, but G.sepium had DMD higher in dry season. The OMD L.leucocephala and G. sepium higher during the dry season, while the S.grandiflora had higher during the rainy season. Natural grass and P.purpuroides had DMD and OMD higher during the rainy season. Dry matter intake (kg/head/day) of cattle during dry season was higher (P<0.01), but rainy season ADG and FCR was higher (P<0.01). It can be concluded the feed used by farmers during the rainy season was more varied, with better quality. As a result, the performance of Bali cattle fattened was higher in the rainy season than in the dry season.